Building a Dialogue to Promote Microfinance Best Practices in South America - Goldberg, Mike; Palladini, Eric (World Bank, Washington, DC, 2012)
This note provides a summary of how the Bank established an eight-part distance learning series for dialogue with South American micro-financing institutions (MFIs). The objectives of the dialogues were to: (1) highlight the Bank's ability to mobilize international technical expertise in microfinance; (2) strengthen MFIs by disseminating new knowledge and technological best practices; (3) promote the sharing of experiences and lessons learned; and (4) promote greater ties among the MFIs in the region. The events became an ongoing forum to provide technical assistance to microfinance networks in Bolivia, Colombia, Ecuador, and Peru.